2012
DOI: 10.1016/j.cell.2012.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Role of TAZ as Mediator of Wnt Signaling

Abstract: Wnt growth factors are fundamental regulators of cell fate, but how the Wnt signal is translated into biological responses is incompletely understood. Here, we report that TAZ, a biologically potent transcriptional coactivator, serves as a downstream element of the Wnt/β-catenin cascade. This function of TAZ is independent from its well-established role as mediator of Hippo signaling. In the absence of Wnt activity, the components of the β-catenin destruction complex--APC, Axin, and GSK3--are also required to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
452
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(475 citation statements)
references
References 40 publications
20
452
2
1
Order By: Relevance
“…We evaluated gene signatures comprising MAPK or β-catenin target genes, as well as signature genes enriched in stem cells or proliferative committed TA cells of the intestinal epithelium. [29][30][31][32] As expected, we found that a signature of MAPK target genes was strongly induced by BRAF V600K in ISCs when compared with luciferase-expressing control ISCs. However, signatures of β-catenin target genes were not significantly changed.…”
Section: Above)supporting
confidence: 86%
“…We evaluated gene signatures comprising MAPK or β-catenin target genes, as well as signature genes enriched in stem cells or proliferative committed TA cells of the intestinal epithelium. [29][30][31][32] As expected, we found that a signature of MAPK target genes was strongly induced by BRAF V600K in ISCs when compared with luciferase-expressing control ISCs. However, signatures of β-catenin target genes were not significantly changed.…”
Section: Above)supporting
confidence: 86%
“…At the heart of the canonical Wnt signaling pathway is the silencing of glycogen synthase kinase 3b (GSK3b), which, if active, phosphorylates the N terminus of any cytoplasmic b-catenin not used in cell-cell adhesion (Hart et al 1999;Liu et al 1999a). GSK3b forms a complex with Axin, a priming kinase for b-catenin called casein kinase 1a (CK1a), adenomatous polyposis coli (APC), and YAP/TAZ Lee et al 2003;Azzolin et al 2012). Also present in this so-called destructive complex is the b-transducin repeat-containing protein (b-TrCP) E3 ligase, which ubiquitinates phosphorylated b-catenin and targets it for proteasomal degradation ( Fig.…”
Section: Overview Of Wnt Signaling Pathwaysmentioning
confidence: 99%
“…A particularly intriguing intersection is the pathway involving the YAP/TAZ transcriptional regulators, which govern proliferation in a variety of cells and tissues. YAP/ TAZ can be regulated by mechanosensing, a feature that can block its inhibitory kinase, Hippo, and enable YAP/ TAZ to translocate into the nucleus and function as transcriptional cofactors for the TEAD family of DNAbinding proteins (Varelas et al 2010;Heallen et al 2011;Azzolin et al 2012;Imajo et al 2012;Aragona et al 2013). Hippo signaling can also regulate b-catenin, and, reciprocally, YAP/TAZ can inhibit Wnt/b-catenin signaling (Varelas et al 2010;Heallen et al 2011;Imajo et al 2012).…”
Section: Yap/taz and Wnt/b-catenin: Juggling Proliferation Between Twmentioning
confidence: 99%
“…Recently, Yes‐associated protein 1 (YAP1) and related transcriptional coactivator TAZ [alternative name for WW domain‐containing transcription regulator 1 (WWTR1)] were discovered as critical components of the β‐catenin destruction complex (Azzolin et al ., 2014). Wnt signaling stabilizes TAZ and promotes TAZ‐dependent transcriptional activation of genes regulated by the TEA domain/Transcription Enhancer Factor (TEAD) family of transcription factors, the main binding partners of both TAZ and YAP1 (Azzolin et al ., 2012). Moreover, β‐catenin and Yes‐associated protein (YAP) act as coactivators of the T‐BOX 5 (TBX5) nuclear factor (Rosenbluh et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%